Chemical and perfusion markers as predictors of moyamoya disease progression and complication types - Jae Hyun Kim; Hanwool Jeon; Moinay Kim; Joonho Byun; Yeongu Chung; Si Un Lee; Wonhyoung Park; Jung Cheol Park; Jae Sung Ahn; Seungjoo Lee (Scientific Reports, 2024)
Abstract To investigate the association between chemical markers (triglyceride, C-reactive protein (CRP), and inflammation markers) and perfusion markers (relative cerebral vascular reserve (rCVR)) with moyamoya disease progression and complication types. A total of 314 patients diagnosed with moyamoya disease were included. Triglyceride and CRP levels were assessed and categorized based on Korean guidelines for dyslipidemia and CDC/AHA guidelines, respectively. Perfusion markers were evaluated using Diamox SPECT. Cox proportional hazard analysis was performed to examine the relationship between these markers and disease progression, as well as complication types (ischemic stroke, hemorrhagic stroke, and rCVR deterioration). Elevated triglyceride levels (≥ 200) were significantly associated with higher likelihood of end-point events (HR: 2.292, CI 1.00–4.979, P = 0.03). Severe decreased rCVR findings on Diamox SPECT were also significantly associated with end-point events (HR: 3.431, CI 1.254–9.389, P = 0.02). Increased CRP levels and white blood cell (WBC) count were significantly associated with moyamoya disease progression. For hemorrhagic stroke, higher triglyceride levels were significantly associated with end-point events (HR: 5.180, CI 1.355–19.801, P = 0.02). For ischemic stroke, severe decreased rCVR findings on Diamox SPECT (HR: 5.939, CI 1.616–21.829, P < 0.01) and increased CRP levels (HR: 1.465, CI 1.009–2.127, P = 0.05) were significantly associated with end-point events. Elevated triglyceride, CRP, and inflammation markers, as well as decreased rCVR, are potential predictors of moyamoya disease progression and complication types. Further research is warranted to understand their role in disease pathophysiology and treatment strategies.